Hubungan Manajemen Latihan dengan Parameter Pola Jalan pada Anak dengan Cerebral Palsy (CP) - Sofiatun; Meilisa Puspita Handayani; Meyla Rossa; Sri Mardjiati Mei Wulan (Journals of Ners Community, 2023)
Â  Background: Cerebral Palsy is a non-progressive disorder due to the presence of lesions in the brain. This affects the early development of the baby which affects the ability to move, balance, and posture. Cerebral Palsy is causes of children's motor disabilities, mostly in decreasing the flexibility of lower extremity muscles and affecting the pattern of walking in sufferers. Objectives: This study aims to identify the relationship between exercise management and the Dynamic Gait Index (DGI) as a parameter of walking patterns in children with cerebral palsy. Research Design: This study used a descriptive observational-analytical cross sectional study in 15 cerebral palsy patients aged 4 to 19 years with GMFCS I-II and had received an exercise program of at least 8 weeks. Data analysis using the Spearman test on SPSS Statistics 26.0. Result: Obtained the value of p = 0.001 (p < 0.01) and the correlation coefficient (Ï) = 0.848 on the relationship of exercise intensity and road pattern parameters. Â Conclusion: There is a relationship between exercise management and gait pattern parameters.